Does The Investment Opportunity Set Strengthen The Effect of Profitability, Managerial Ownership and Capital Structure on Firm Value? - Garnis Mulya Ningrum; Khomsiyah Khomsiyah (Politeknik Siber Cerdika Internasional, 2023)
This study aims to examine the effect of profitability, managerial ownership, and capital structure on firm value and to test whether the investment opportunity set strengthens Profitability, managerial Ownership, and capital structure on firm value. As part of the purposive sampling method used in this study, which leverages secondary data, 60 data points were collected from 15 firms between 2018 and 2021 that met the required requirements. Moderate Regression Analysis (MRA) is the method of data analysis used in this study. According to the findings of the study, profitability has not to effect on firm value, managerial ownership has a positive effect on firm value, capital structure has a positive effect on firm value, investment opportunity sets weaken the relationship between profitability on firm value, investment opportunity sets weaken the relationship between managerial ownership on firm value, and investment opportunity set strengthens the relationship between capital structure on firm value. This research's objective was to ascertain if the investment opportunity set enhances both the direct and indirect impacts of Profitability, managerial Ownership, and capital structure on firm value. Based on the conclusions and limitations that exist, there are several suggestions addressed to parties related to research regarding the role of investment opportunity sets in moderating Profitability, managerial Ownership, and capital structure on firm value.